Determinasi Keputusan Pendanaan pada Perusahaan Startup Digital di Indonesia: Perspektif Pecking Order Theory - Lia Nurina; Napiajo Napiajo (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the determinants of financing decisions in Indonesian digital startups within the framework of the Pecking Order Theory (POT). The theory predicts a financing preference order starting from internal funds, followed by debt and equity. However, the distinctive characteristics of digital startups—such as the dominance of intangible assets, volatile cash flows, and rapid scaling requirements—may alter this hierarchy. This research employs an explanatory quantitative design using secondary data and purposive sampling of startups with verifiable information on founding year, firm scale, and financing history. Financing decisions are classified into internal financing, debt, and equity, and analyzed using a multinomial logit model. The main explanatory variables include firm size, age, growth stage, business risk, asset tangibility, internal funding strength, financing deficit, and prior funding experience, with subsector and year controls. The results indicate that stronger internal funds significantly reduce the likelihood of external financing, while financing deficits increase the probability of using both debt and equity. Firm size enhances access to external financing, whereas firm age and asset tangibility are more closely associated with debt financing. In contrast, the scaling stage, higher risk levels, and previous funding records tend to drive a preference for equity over debt. These findings suggest that POT applies conditionally to Indonesian digital startups, where direct transitions from internal financing to equity are more prevalent during rapid growth phases.